Handbook on the physics and chemistry of rare earths. - Bunzli, J.-C. G., 1944-; Pecharsky, Vitalij K. (Handbook on the physics and chemistry of rare earths ;, 2011)
This continuing authoritative series deals with the chemistry, materials science, physics and technology of the rare earth elements in an integrated manner. Each chapter is a comprehensive, up-to-date, critical review of a particular segment of the field. The work offers the researcher and graduate student a complete and thorough coverage of this fascinating field. Authoritative Comprehensive Up-to-date Critical.